Incidence of influenza virus infections confirmed by serology in children and adult in a suburb community, northern China, 2018‐2019 influenza season. Issue 2 (25th September 2020) - Xu, Cuiling; Liu, Ling; Ren, Binzhi; Dong, Libo; Zou, Shumei; Huang, Weijuan; Wei, Hejiang; Cheng, Yanhui; Tang, Jing; Gao, Rongbao; Feng, Lizhong; Zhang, Ruifu; et al.
Abstract: Background: In mainland China, seasonal influenza disease burden at community level is unknown. The incidence rate of influenza virus infections in the community is difficult to determine due to the lack of well‐defined catchment populations of influenza‐like illness surveillance sentinel hospitals. Objectives: We established a community‐based cohort to estimate incidence of seasonal influenza infections indicated by serology and protection conferred by antibody titers against influenza infections during 2018‐2019 influenza season in northern China. Methods: We recruited participants in November 2018 and conducted follow‐up in May 2019 with collection of sera every survey. Seasonal influenza infections were indicated by a 4‐fold or greater increase of hemagglutination inhibition (HI) antibody between paired sera. Results: Two hundred and three children 5‐17 years of age and 413 adults 18‐59 years of age were followed up and provided paired sera. The overall incidence of seasonal influenza infection and incidence of A(H3N2) infection in children (31% and 17%, respectively) were significantly higher than those in adults (21% and 10%, respectively). The incidences of A(H1N1)pdm09 infection in children and adults were both about 10%, while the incidences of B/Victoria and/Yamagata infection in children and adults were from 2% to 4%. HI titers of 1:40 against A(H1N1)pdm09 and A(H3N2) viruses were associated with 63% and 75% protection against infections with the two subtypes, respectively. Conclusions: In the community, we identified considerable incidence of seasonal influenza infections. A HI titer of 1:40 could be sufficient to provide 50% protection against influenza A virus infections indicated by serology.